Bank competition and international financial integration: Evidence using a new index - Gurnain Kaur Pasricha (Bank of Canada, 2010)
This paper finds a strong empirical link between domestic banking sector competitiveness and de facto international integration. De-facto international integration is measured through a new index of financial integration, which measures, for deviations from covered interest parity, the size of no-arbitrage bands and the speed of arbitrage outside the no-arbitrage band. The strong empirical link between de-facto integration and domestic financial sector competitiveness allows us to reinterpret the recent literature on the benefits and costs of international financial integration. This literature has emphasized the development of domestic markets as a precondition to benefiting from international integration. This paper offers an alternative view. Lack of competition in domestic financial systems may prevent countries from reaping the benefits of international integration simply because it prevents them from being integrated in a meaningful way - that of price equalization. This finding suggests that financial sector consolidation of the type recently witnessed in the crisis environment may have negative consequences for countries' de-facto international financial integration. Another important result of the paper is that the level of de-jure controls have a limited association with de-facto integration, particularly for developing economies.
Keywords: F32; G15; G21; 330; Econometric and statistical methods; Financial markets; International topics; Internationale Wirtschaftsbeziehungen; Wirtschaftsintegration; Bank; Wettbewerb; Kanada